Buddhist and Kantian Enlightenment Projects - Ibana, Ranier A (Archīum Ateneo, 2019)
The Buddha taught in the Kalama Sutta that one must abide by religious teachings only “when you yourselves know” the consequences of these doctrines in everyday life. This principle is reinforced and corroborated by stories that surround the life of the Buddha. Not unlike Kant’s essay, “What is Enlightenment?,” the Kalama Sutta also aims to liberate humans from distorted perceptions filtered by aristocratic social contexts and naïve world views. Kant’s revolutionary project, however, makes a distinction between the public and private uses of reason and applies the enlightenment doctrine to the former while allowing for temporary compromises in the latter. The Buddha, on the other hand, is not known to make such a distinction and emphasizes personal emancipation from the illusions of the transitory world. The Buddha’s awakening to the experience of suffering, however, goes further than Kant’s Enlightenment project to include non-human beings within the ambit of its objects of compassion and can therefore more adequately address ecological concerns.